STATISTICAL ANALYSIS OF INTERRELATIONS BETWEEN ROD CHARACTERISTICS AND DEFORMATION PROPERTIES OF PRODUCED WIRE - A. N. Chichko; A. V. Vedeneev; O. A. Sachek; L. A. Feklistova (Литьë и металлургия)
Analysis of interconnection between characteristics of rolled wire and deformational characteristics of produced of it wire in conditions of RUP «BMZ» is investigated. It is shown that the higher degree of wire delamination the lower characteristics of curling.